Drying edible jellyfish (Lobonema smithii) using a parabolic greenhouse solar dryer - S. Maisont; W. Samutsri; A. Sansomboon; P. Limsuwan (My University, 2022)
Thailand is one of Southeast Asia’s top exporters of salted edible jellyfish. Jellyfish products are generally exported in the form of semi-dried jellyfish. A recent survey on jellyfish distribution in coastal areas in the Gulf of Thailand and the Andaman Sea indicated that most edible jellyfish in the area belong to Lobonema smithii and Rhopilema hispidum. Drying is an alternative method to preserve food products. In this work, parabolic roof shape greenhouse solar drying of edible jellyfish (Lobonema smithii) was studied, and the quality of the dried jellyfish was assessed. The solar dryer system has a 300 kg loading capacity for jellyfish and the resulting dried and rehydrated jellyfish products are described. The moisture content of dried jellyfish decreased to 7.05-11.70% (wb) from 91-92% (wb) after drying for three days and the protein, fat, crude fibre, ash, and carbohydrate content of the dried jellyfish were 68.68%, 0.74%, 0.43%, 9.27%, and 4.67%, respectively. The moisture of the rehydrated jellyfish increased to 37.67-39.07% (wb) after soaking in distilled water for 5 hrs. In terms of colour, the rehydrated jellyfish products were found to be highly similar to salted jellyfish products.
Keywords: Marine Invertebrate Physiology and Ecology